Economic security and strategic adaptation of construction enterprises in the phases of crisis changes and turbulence - Kucherenko, O.; Bartko, V.; Konchakivskyi, O.; Maliarenko, O.; Fedorova, Ya. (Ways to Improve Construction Efficiency, 2022)
The research focuses on identifying innovative approaches to improving management and enhancing the competitiveness of domestic enterprises engaged in construction development. The emphasis is placed on the theoretical and methodological framework for studying enterprise resilience in a dynamic environment. The article is grounded in the concept of innovative development of construction development enterprises, defined by the combination of internal capabilities and external market impulses that together form the field of economic and managerial predictors. In a dynamic environment, where demand is cyclical, regulations and standards are rapidly updated, and supply chains are periodically subject to shocks, the key role is played by the firm’s dynamic capabilities: anticipating changes, quickly reallocating resources, scaling proven solutions, and phasing out ineffective initiatives. A defining dominant is ambidexterity — the ability to simultaneously exploit current business models while exploring new ones, for example, combining serial-typical solutions with pilot digital services for residents and asset management platforms. Risk and resilience management emerges as an independent predictor of innovation when scenario-based demand models, cost sensitivity to resource inflation, multichannel supply chains, and contractual mechanisms that distribute time and quality risks are implemented. The integration of ESG criteria and full life-cycle costing shifts the focus from minimizing initial costs to minimizing total ownership costs, opening space for material and engineering innovations justified over a 20–30 year horizon. The further development of business process analytics has been influenced by systemic and process approaches, where the enterprise began to be viewed as an open dynamic system. New models of performance evaluation emerged through integrated performance indicators that included not only financial results but also time indicators, quality, customer satisfaction, and risk level. This reflected the transition to understanding business processes as organizational flows sensitive to external factors and internal synergistic effects.